Tradições e preconceitos no ensino superior : uma leitura hermenêutica da lei de cotas - Camargo, Bianca (2025)
This dissertation sets out to understand the effects of the implementation of the Quotas Law (Lei de Cotas) in Brazilian higher education institutions, adopting a historical and hermeneutic perspective. More than just an instrument of access, the law is analyzed as a transformative policy, capable of confronting structural racism and provoking profound changes in the practices and values that shape the daily life of universities. The research is guided by the following question: from a hermeneutic perspective, how can the Quotas Law reconfigure traditions and prejudices in higher education, contributing to the confrontation of structural racism? Based on this problematization, the general objective is to examine, in light of hermeneutics, how the Quotas Law, in association with student retention policies, contributes to transforming practices shaped by exclusionary institutional and symbolic traditions, and to confronting structural prejudices within the university environment. This qualitative research is based on a critical bibliographic review that includes theoretical works, institutional documents, and relevant legislation. The theoretical framework is grounded in fundamental voices in the fight against racial inequalities in Brazil, with emphasis on: Kabengele Munanga, who challenges the myth of racial democracy and highlights the importance of recognizing Black and Indigenous identities as part of a historical reconstruction process; Sueli Carneiro, who deepens the debate on structural racism, emphasizing the centrality of reparatory policies as instruments of social justice; and Joaquim Barbosa, whose contributions in the legal field offer a constitutional basis for affirmative action, reinforcing the role of the State in correcting historically entrenched inequalities. The methodology adopts hermeneutics both as a stance and as an interpretive method, seeking to understand the historical and social meanings attributed to affirmative policies. The analysis is conducted through the lens of Hans-Georg Gadamer’s philosophical hermeneutics, particularly his work Truth and Method, which conceives understanding as a historical and dialogical process, shaped by traditions and prejudices. The body of the dissertation is structured into three main chapters. The first discusses the historical trajectory of affirmative action and the consolidation of the Quotas Law in Brazil, emphasizing the exclusionary racist tradition that marks Brazilian higher education. The second addresses mechanisms aimed at inclusion and student retention in higher education, highlighting the prejudices linked to racial exclusion, with particular attention to the ideology of meritocracy. The third chapter constitutes the analytical core of the research, critically exploring the concepts of tradition and prejudice, while introducing the hermeneutic notion of dialogue, demonstrating how the Quotas Law challenges hegemonic narratives, generates shifts in meaning, and enables new forms of belonging and recognition in higher education. As practical implications, the study highlights the importance of strengthening student retention policies and critically reviewing institutional cultures, recognizing that confronting structural racism in higher education—sustained by social and institutional traditions and prejudices—requires not only political actions, but also profound transformations in the ways knowledge is produced and legitimized, which demand critical dialogue among all stakeholders involved.